Vectorial GP for Alzheimer’s Disease Prediction Through Handwriting Analysis - Azzali, Irene (2022)
Azzali, I., Cilia, N. D., De Stefano, C., Fontanella, F., Giacobini, M., & Vanneschi, L. (2022). Vectorial GP for Alzheimer’s Disease Prediction Through Handwriting Analysis. In J. L. Jiménez LaredoJ, J. I. Hidalgo, & K. O. Babaagba (Eds.), Applications of Evolutionary Computation: 25th European Conference, EvoApplications 2022, Held as Part of EvoStar 2022, Madrid, Spain, April 20–22, 2022, Proceedings (pp. 517-530). (Lecture Notes in Computer Science; Vol. 13224). Springer. https://doi.org/10.1007/978-3-031-02462-7_33 ----------------------This work was partially supported by FCT, Portugal, through funding of projects BINDER (PTDC/CCI-INF/29168/2017) and AICE (DSAIPA/DS/0113/2019). This work was also supported by MIUR (Minister for Education, University and Research, Law 232/216, Department of Excellence).